MAKNA MANTRA PATTUIK TAU GULA BERDASARKAN PEMBACAAN HEURISTIK PADA TRADISI MASYARAKAT MAKASSAR DI DESA BORONGTALA KABUPATEN JENEPONTO (TINJAUAN SEMIOTIKA RIFFATERRE): THE MEANING OF MANTRA PATTUIK TAU GULA BASED ON HEURISTIC READING IN THE TRADITION OF MACASSAR PEOPLE IN BORONGTALA VILLAGE, JENEPONTO DISTRICT (RIFFATERRE SEMIOTICS REVIEW) - Asnani; Fatimah Yunus, Andi; Faisal (Journal of Applied Linguistics and Literature, 2024)
This study aims to describe the meaning of Mantra Pattuik Tau Gula of Makassar Community Tradition in Borongtala Village, Jeneponto Regency based on heuristic reading. The type and design of this research is descriptive qualitative research. The data in this study is the meaning of the pattuik tau gula mantra which is the primary data used in the treatment process based on informants about the meaning of the Pattuik Tau Gula Mantra. The results of this study found that there are nine pattuik tau gula therapy mantras including four pattuik tau gula therapy mantras (wet), four pattuik tau gula therapy mantras (dry) and one pattuik tau gula wound mantra. In the heuristic reading, some pattuik tau gula therapy mantras have different meanings, but there are also some pattuik tau gula mantras that have the same meaning and words when interpreted word by word and sentence by sentence. Overall, the meanings contained in the nine pattuik tau gula therapy mantras describe: requests for healing, expulsion of evil creatures and protection to Allah Swt.